Project [Murmur] and the Performativity of Space - Eaket, Chris (Theatre Research in Canada / Recherches théâtrales au Canada, 2008)
In The Practice of Everyday Life, Michel de Certeau asserts that "what the map cuts up, the story cuts across" (129), stressing the role of a nomadic, storytelling subject in the production of space. The [murmur] project, an experiment in site-specific psychogeography and cybercartography (http://murmurtoronto.ca), explores the relationship between spaces represented cartographically, spaces lived through audience explorations, and the (imaginary) representational spaces generated through oral histories. The site-specific stories of participants, delivered by cell phone to audience members at specially marked sites, transform reified places into lived spaces that the user can explore and interpret in real time. [murmur] situates the subject simultaneously at the site of the referent and within an imaginary (aural) space of representation, compelling the audience member to reconcile the two. In exploring the representational frame (and its boundaries), the user becomes an active participant in the semiotic processes of spatial production. Thus, [murmur] can be seen as an important intervention: rather than accepting the reified city as a given, or acting on the subject in a way that limits semiosis, the places the project constructs through discourse encourage the emergence (or becoming) of a nomadic subject who produces new meanings through a process of spatial dialectics. Equally important, [murmur] foregrounds the need to rethink cities not as sets of buildings and objects, but rather as places where historical and subjective information is latent in every materiality and, similarly, where the materiality of city is seen as the result of the performative processes of spatial production. Résumé Dans L’invention du quotidien, Michel de Certeau écrit que « là où la carte découpe, le récit traverse » (190), mettant ainsi en relief le rôle du narrateur nomade dans la production de l’espace. Le projet [murmur], une exploration de la psycho-géographie et de la cybercartographie localisées (http://murmurtoronto.ca), s’intéresse au rapport qu’entretiennent les espaces représentés par cartographie, ceux dans lesquels circulent un auditoire et les espaces représentatifs (imaginaires) créés par l’histoire orale. Les récits localisés que livrent les participants par téléphone cellulaire aux membres du public dans des sites signalés transforment des lieux réifiés en espaces vécus que l’utilisateur peut explorer et interpréter en temps réel. [murmur] inscrit le sujet à la fois dans le site du référent et au cœur d’un espace de représentation (sonore) imaginé tout en invitant le public à réconcilier les deux espaces. En explorant le cadre représentationnel (et ses frontières), l’utilisateur participe activement aux processus sémiotiques de la production spatiale. Ainsi, on peut dire de [murmur] qu’il s’agit d’une intervention importante : au lieu d’accepter la ville réifiée telle qu’elle est ou d’agir sur le sujet de façon à limiter la sémiose, les espaces que construit ce projet par son discours encouragent l’émergence (ou le « devenir ») d’un sujet nomade qui produit de nouveaux sens par une dialectique de l’espace. De façon tout aussi importante, [murmur] souligne qu’il faut repenser la ville non plus comme un ensemble d’édifices et d’objets, mais comme un lieu où circulent des renseignements historiques et subjectifs présents de façon latente dans tous les matériaux. De même, la matérialité de la ville serait conçue comme le résultat des processus performatifs de la production spatiale.